Detection and Characterization of Mycobacterial Infections Occurring in Phacochoerus africanus (Gmelin, 1788) (Common Warthog) - Roos, Eduard Otto (Stellenbosch : Stellenbosch University, 2018)
Thesis (PhD)--Stellenbosch University, 2018.